If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 5y + 16 Reorder the terms: y = 16 + 5y Solving y = 16 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. y + -5y = 16 + 5y + -5y Combine like terms: y + -5y = -4y -4y = 16 + 5y + -5y Combine like terms: 5y + -5y = 0 -4y = 16 + 0 -4y = 16 Divide each side by '-4'. y = -4 Simplifying y = -4
| 6x+2=4x-y | | 4(a^2+11a-48)=0 | | -9+7r=-5r | | 10t-.83t^2=14 | | 3x+11=3+21 | | x-15/16=-1.0364 | | 4a-2b=10 | | w+63=8w | | 43+5y-6=16y-11-3y | | 2(3r-7)+4(3r+2)=(5r+9)+3 | | 3x+11=3x-21 | | 690x-(18000+60x+x^2)=p | | 17+8z=17 | | 7.9x-3.4=4.5 | | 6/9x=42 | | 130/0.25 | | 3.6p-5=13.9 | | 3.6p-5=13 | | (360-230)/0.25 | | t/-710 | | -9=.45m | | 9360-230)/.25 | | 5x+19=x-7 | | 26+16x=15x | | 54=16v | | X+2=-10+4x | | 6(0.5+1)= | | (8x/5)/(1-3/10) | | 9546x-3440=86(111x-40) | | 6x+7=-5+7x | | 8c-2d= | | 7x+2=2-2x |